Coaching Employees through Difficult Situations. - Lotardo, Elizabeth; Earle McLeod, Lisa (linkedin.com, 2018)
In this scenario-based course, discover how to coach someone who is older than you, how to motivate employees who have been demoted or promoted, and more.